Research Progress of Hydromorphone in Clinical Application - Liu, L; Xu, M; Wang, J; Hu, Y; Huang, Z (Physiological research, 2025)
A common opioid analgesic for cancer pain and, to a lesser extent, non-cancer pain, is hydromorphone (HM). Oral formulations as well as subcutaneous, intravenous, and other routes are frequently used for its administration. Its pharmacokinetics and pharmacodynamics have also been extensively researched. This article examines the pharmacological properties of hydromorphone and the development of its use both domestically and internationally with the goal of serving as a reference for the sensible clinical use of this medication. Key words Hydromorphone, Pharmacological action, Route of administration, Cancer pain, Adverse effects.
Keywords: Animals; Pain; hydromorfon; bolest; lidé; opioidní analgetika; nádorová bolest; zvířata; Hydromorphone; Analgesics, Opioid; Cancer Pain; Humans